1993
DOI: 10.1177/017084069301400105
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Political Climate and Job Attitudes

Abstract: The present study examines the relationships between perceived Organizational Politics (OP) and job attitudes. Questionnaires containing scales of perceived OP climate and job attitudes were administered to a sample of 200 employees in several organizations. It was found that variables reflecting on the employee's status in the organization such as Gender and Supervisory Position moderate the relationships between perceptions of organizational politics and job attitudes. The association between climate and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
110
1
16

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 22 publications
(18 reference statements)
8
110
1
16
Order By: Relevance
“…Subsequent studies have found evidence for hypothesized relationships. For example, in the case of organizational antecedents, findings suggest that employees perceive politics to be more prevalent at higher organizational levels (Ferris & Kacmar, 1992), although Drory (1993) found that employees at lower (non-managerial) levels were more likely 8 than those at higher levels to describe their organizational environment as political. There is also support for hypothesized links between perceptions of politics and consequences for employees.…”
Section: Perceptions Of Politicsmentioning
confidence: 95%
See 2 more Smart Citations
“…Subsequent studies have found evidence for hypothesized relationships. For example, in the case of organizational antecedents, findings suggest that employees perceive politics to be more prevalent at higher organizational levels (Ferris & Kacmar, 1992), although Drory (1993) found that employees at lower (non-managerial) levels were more likely 8 than those at higher levels to describe their organizational environment as political. There is also support for hypothesized links between perceptions of politics and consequences for employees.…”
Section: Perceptions Of Politicsmentioning
confidence: 95%
“…For example, in the case of organizational antecedents, findings suggest that employees perceive politics to be more prevalent at higher organizational levels (Ferris & Kacmar, 1992), although Drory (1993) found that employees at lower (non-managerial) levels were more likely…”
Section: Perceptions Of Politicsmentioning
confidence: 97%
See 1 more Smart Citation
“…A presença da política como um sistema de influência e poder inerente aos diversos tipos de instituições vem sendo investigada sob a ótica da percepção disfuncional que os funcionários têm do fenômeno e seus impactos negativos nas organizações (Drory, 1993;Kacmar & Ferris, 1991;Miller, Rutherford, & Kolodinsky, 2008). Diversas definições da política organizacional sob essa abordagem foram cunhadas por autores expoentes nos últimos 50 anos e suas perspectivas ilustram a forma como o fenômeno é percebido.…”
Section: A Percepção De Política Nas Organizaçõesunclassified
“…ÖP yazını 20 yıllık bir geçmişe sahip olmasına rağmen, ÖP'nin tanımı üzerinde bir fikir birliğine oluşmadığı belirtilmektedir. (Drory ve Romm 1989;Vigoda-Gadot, 2010 Drory (1993) gayri resmi temelli ve çelişkili yönetim tarzlarıyla ortaya çıkan şahsi çıkar koruma ve geliştirme çabaları şeklinde tanımlamıştır. En çok kabul gören tanımlamalardan birinin sahibi olarak kabul edilen Vigoda'nın (2000) da aynı noktalara vurgu yaparak, ÖP'yi işgörenlerin gözünde diğer işgörenlerin şahsi çıkarlarını korumak ve geliştirmek için sergiledikleri davranışlar olarak tanımladığı görülmektedir.…”
Section: Algılanan öRgütsel Politikaunclassified